Slovenian Translation, Cross-Cultural Adaptation, and Content Validation of the Updated Oslo Sports Trauma Research Center Questionnaire on Health Problems (OSTRC-H2) - Drole, Kristina; Steffen, Kathrin; Paravlic, Armin (Orthopaedic journal of sports medicine, 2024)
BACKGROUND: The updated Oslo Sports Trauma Research Questionnaire on Health Problems (OSTRC-H2) has been translated into a limited set of languages and lacks full validation of its new measures. PURPOSE: To (1) translate, cross-culturally adapt, and evaluate the measurement properties of the OSTRC-H2 for the Slovenian population and (2) investigate the construct validity for the severity score and time lost due to a health problem. STUDY DESIGN: Cohort study (diagnosis); Level of evidence, 3. METHODS: The OSTRC-H2 was translated from English to Slovenian (OSTRC-H2-SLO) according to international guidelines. A 15-week study was conducted among 188 elite athletes, with a test-retest performed in the 10th week. Internal consistency, reliability, content validity, feasibility, and potential ceiling effects were investigated. Internal consistency was measured using the Cronbach alpha coefficient, while reliability was measured with the intraclass correlation coefficient (ICC). Construct validity was measured with the Spearman rank correlation coefficient (rS). RESULTS: There was a 95% response rate and an 18% mean weekly prevalence of health problems. The OSTRC-H2-SLO showed excellent test-retest reliability (ICC, 0.94 [95% CI, 0.67-0.99]), with a Cronbach α of .93. A strong positive correlation was found between the OSTRC-H2-SLO severity score and days lost due to an acute injury (rS = 0.754), overuse injury (rS = 0.785), and illness (rS = 0.894) (P < .001 for all). Moderate to strong negative correlations were observed between severity score and total load (training and competition load in hours) as well as between days lost and total load (P < .001 for all). CONCLUSION: The OSTRC-H2-SLO was found to be valid, reliable, and well accepted among Slovenian athletes. The authors confirmed the questionnaire's construct validity and identified total load as an indicator of an increase in the severity score. REGISTRATION: NCT05471297 (ClinicalTrials.gov identifier).